(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Open innovation is gaining recognition as a strategic approach for the industrial sector to enhance competitiveness and adaptability. This study investigates the primary determinants influencing the implementation of open innovation (OI) in Indian manufacturing firms, a context that is presently insufficiently addressed in the existing literature. Innovation theory and the resource-based view, seven antecedents are examined: competitive advantage, government support and policy, innovation and flexibility, knowledge absorptive capacity, market uncertainty, organizational readiness, and proactivity. This study aims to determine the factors that influence Indian manufacturing companies’ decision to adopt open innovation, including organizational readiness, competitive advantage, government policy and support, innovation and flexibility, knowledge absorption capacity, market uncertainty, and proactiveness. The study employed a descriptive and causal design and used primary data gathered from 398 senior executives in the manufacturing sector. We used a structured questionnaire that was based on items that had been validated in previous research to gather data. The proposed hypotheses were tested and the significance of the correlations between the constructs was evaluated using Structural Equation Modeling via Partial Least Squares (SEM-PLS). The results show that organizational readiness, competitive advantage, innovation and flexibility, market uncertainty, and proactiveness all have a major impact on OI adoption. Organizational readiness was more important than government support or the capacity to take in new information. These results show that internal strategic and structural capabilities of Indian businesses are more significant in promoting OI practices than external institutional support. This work adds to the theory of innovation in emerging economies by providing a tested structural model that can be applied to the manufacturing sector in India. It illustrates that lawmakers need to change the way they aid businesses and that businesses need to use their own skills. The study shows that innovation methods that work in one place may not work in another, especially in economies with limited resources and different types of institutions.